Long-term outcome of a treat-to-target strategy in late-onset rheumatoid arthritis with chronic lung disease: 5-year results of a prospective observational study - Manami Nomura; Takahiko Sugihara; Hiroyuki Baba; Tadashi Hosoya; Mari Kamiya; Tatsuro Ishizaki; Takumi Matsumoto; Kanae Kubo; Fumio Hirano; Masayo Kojima; Nobuyuki Miyasaka; Shinsuke Yasuda; et al. (Arthritis Research & Therapy)
Abstract Background Controlling disease activity and improving physical function would be more difficult in patients with late-onset rheumatoid arthritis (LORA) who have chronic lung disease (CLD) at baseline. Our aim was to evaluate 5-year outcomes of following a treat-to-target (T2T) strategy targeting low disease activity (LDA) in LORA with CLD. Methods Data from 197 methotrexate (MTX)-naïve LORA patients (mean age 74.4 years) from a prospective, monocentric registry were analyzed. Patients were treated with MTX if they had one or more poor prognostic features. If they had interstitial lung disease (ILD), tacrolimus could be administered instead of MTX at the discretion of the attending physician. If patients exhibited no response according to the European League Against Rheumatism criteria at week 12 or had not achieved LDA by week 24, biological disease-modifying antirheumatic drugs (bDMARDs) were started targeting LDA. The primary outcomes were the 5-year simplified disease activity index (SDAI) remission and Health Assessment Questionnaire Disability Index (HAQ-DI) ≤ 0.5 by non-responder imputation analysis. Secondary outcomes were serious adverse events (SAEs). Results Of the 197 LORA patients, 47 had CLD at baseline. The proportion of patients using MTX at baseline was significantly lower in those with than without CLD. Tacrolimus was initiated in 25.5% of the CLD group. The proportion of patients on bDMARDs was higher in those with CLD at year 5. Achievement of SDAI remission at year 5 was 29.8% in patients with CLD and 44.0% in those without CLD (p = 0.555). Achievement of HAQ-DI ≤ 0.5 at year 5 was 36.2% and 45.3% in patients with and without CLD, respectively (p = 0.939). Non-adherence to T2T due to comorbidities or adverse events was observed in 34.0% and 18.7% of the patients with and without CLD, respectively (p = 0.027). Infections requiring hospitalization, deterioration of extra-articular manifestations and fractures were more frequently reported as SAEs in patients with CLD, and multivariable analysis showed that patients with CLD had a higher risk of developing these SAEs (adjusted hazard ratio:2.53, 95% CI 1.60–4.00, p < 0.001). Conclusion For LORA patients with CLD, the T2T strategy is effective, but comorbidities and SAEs make the implementation of the T2T more difficult.